An approach to energy and elastic for curves with extended Darboux frame in Minkowski space - Körpınar, Talat; Ünlütürk, Yasin (Amer Inst Mathematical Sciences-Aims, 2020)
In this paper, we construct the energy for the ED-frame field of the first and second kind on an orientable hypersurface in Minkowski space. We obtain the geometric properties of some graphics by way of energy. We apply totally diverse discussion and approach to illustrate bending energy functional for the ED-frame field of the first and second kind. Finally, we have a new relation for angle and energy of the curve on an orientable hypersurface in Minkowski space.
Keywords: energy; ED-frame field; hypersurface; vector fields; bending energy